Impact of untreated dental caries on nutritional status in preschool children - Vallejos Carpio, Joaquin Ignacio (2026)
Untreated dental caries causes significant clinical complications, such as infections (pulpitis, ulcers, fistulas, and abscesses) and tooth loss, which deteriorate the preschool child's quality of life at the functional, aesthetic, and psychosocial levels by compromising vital functions such as mastication and speech. This literature review aims to evaluate the relationship between this pathology and nutritional status in this population. A search was conducted up to May 17, 2024, in databases such as PubMed, Biblioteca Virtual en Salud [Virtual Health Library], EBSCOHost, Scopus, ProQuest, and ScienceDirect, following PRISMA guidelines. Of the 484 records identified, 12 studies met the inclusion criteria. The analysis of the evidence reveals that untreated dental caries is frequently associated with pain and functional limitations that alter food intake, causing dietary changes and possible nutritional deficiencies that negatively impact the child's overall growth and development.